ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS KOPERASI DI KOTA CIREBON TAHUN BUKU 2015 - 2019 - Nuraeni Nuraeni; Dedi Djubaedi; Ayus Ahmad Yusuf (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2023)
Cooperatives in Islamic law, the establishment of cooperatives has the practice of mutual cooperation and help which is ordered by Allah SWT in Q.S Al-Maidah: 2 that legal cooperatives are allowed. Assessment of financial performance in cooperatives is for every member of the cooperative. This study aims to determine how much influence together and each variable on profitability.The method used is a quantitative method with panel data. The population in this study is the number of cooperatives in the city of Cirebon that are active and have implemented the RAT (Annual Member Meeting) of 95 cooperatives. Sampling using the Solvin formula approach, there are 77 cooperatives. The technique of collecting data using the documentation on Cooperative Performance Data in 2015-2019 and interviews obtained directly from the object to be studied, namely the Department of Trade, Cooperatives, Small and Medium Enterprises in Cirebon City.The variables collectively show that 27.6% of profitability by assets, SHU, own capital, business turnover, and several members. Meanwhile, 72.4%Â  by other factors not included in this study, such as leadership policies, management factors, human resources factors, decision factors in the RAT (Annual Member Meeting), and government policy factors.Â Keywords: Cooperatives; Cooperatives in Islam; Profitability